DV8 Physical Theatre Review - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2003)
PALABRAS CLAVE: Living Costs, DV8 Physical Theatre, Lloyd Newson.
Dentro del apartado "Dance Now. Summer in the City".